PENGGUNAAN ALAT PERAGA PADA MATERI BUMI DAN TATA SURYA UNTUK MENINGKATKAN PEMAHAMAN IPA KELAS VII-D SMP NEGERI 1 GEDANGAN - Afifah Naura Salamah; Warmi'anah Warmi'anah; Agung Mulyo Setiawan (UNIB Press, 2023)
This study aimed to improve the student’s understanding of Earth and Solar System in Science subjects through the use of teaching aids. The type of research was collaborative classroom action research between the researcher and teacher. There were two cycles in this study with 4 stages each, namely planning, action, observation, and reflection. The data collection techniques used were observation sheets and tests. Data analysis was carried out using a quantitative descriptive method for the observation sheet and post-test. The results of the study showed that the percentage of learning mastery was 67% in cycle I, both in the first and second meetings. Meanwhile, the percentage of learning mastery in cycle II in the first and second meetings were 75% and 83% respectively. This study concludes that teaching aids can improve the student’s understanding of Earth and Solar System in Science subjects in class VII-D at SMP Negeri 1 Gedangan.